Examine the rural infrastructure development fund (RIDF) in Karnataka - Sathisha (Logistics, supply chain, sustainability and global challenges, 2023)
This study examined the relationship between the Rural Infrastructure Development Fund (RIDF) and agriculture development in Karnataka from 1995 to 2021. While presenting the budget speech for 1995–1996, the honorable union finance minister introduced the RIDF program. The RBI monitors the funding for the RIDF program through NABARD, which has a corpus of Rs. 2,000 crores from commercial and regional banks, among other sources. The program funds the social sector, small to medium irrigation, rural connectivity, and agricultural and related activities. The study evaluated the performance of the RIDF in the State critically. It also observed that several projects remained incomplete even after taking loans from the RIDF. Many states might be unable to take on this financial load due to most governments' dire financial circumstances. Despite this, there have been some physical advancements in rural irrigation, roads, and bridges. The nation's states and regions, however, do not all share the same achievement levels, therefore suggesting necessary steps to ensure proper fund utilization and decrease rural poverty and intra-regional disparity in Karnataka.
Keywords: agriculture development; finance; infrastructure; infrastruktura; Karnataka; podeželje; razvoj kmetijstva; rural area